PCR analysis of mitochondrial DNA polymorphism in N'Dama and Zebu cattle - Suzuki, R.; Kemp, Stephen J.; Teale, A.J. (Wiley, 1992)
A study of polymorphisms of mitochondrial DNA (mtDNA) of West African N'Dama (Bos taurus) and East African Zebu (B. indicus) cattle was carried out to obtain information on maternal phylogenetic relationships between these breeds. A relatively large sample size was made possible by using polymerase chain reaction (PCR) amplification of DNA prepared from small blood samples to generate fragments of two known polymorphic mtDNA regions, one within the gene encoding subunit 5 of NADH dehydrogenase and one encompassing the entire D‐loop. This approach allowed us to achieve a higher resolution restriction analysis on mtDNA from more animals than would have been possible by conventional methods. PCR‐amplified mtDNA of 58 animals from five populations was examined at 26 restriction sites by 16 enzymes. In this way 154 nucleotides of mtDNA were scanned for polymorphism. Six polymorphic sites were located by this means, five of which were within the D‐loop and one of which was within the NADH dehydrogenase 5 gene. None of the polymorphisms observed could be con sidered typical of breed or type.